The role of hypoxic microenvironment in rheumatoid arthritis - Zheng, Qiu-han; Zhai, Ye; Wang, Ying-hang; Pan, Zhi (Frontiers in Immunology, 2025)
Rheumatoid Arthritis (RA) is an autoimmune disease caused by many factors, with a high disability rate, unsatisfactory clinical treatment effect, and unclear pathogenesis. The oxygen level in the joint cavity is significantly reduced, and the hypoxic microenvironment has become a key factor in the pathogenesis and progression of RA. Based on the latest research developments, this review delves into the structure and main functions of the key factor HIF in the hypoxic microenvironment, and expounds the main regulatory mechanisms of HIF. The effect of the hypoxic microenvironment on the pathological changes of RA was analyzed, especially how hypoxia affects the signal transduction of related molecules and cells, thus aggravating the occurrence and development of RA. In addition, the review also discusses emerging therapeutic strategies aimed at targeting the hypoxic pathways, including HIF-1α inhibitors, Hyperbaric oxygen therapy, and the application of traditional Chinese medicine. By providing a comprehensive overview of the interplay between RA and the hypoxic microenvironment, this review aims to provide new perspectives on the underlying mechanisms of RA and provide a theoretical basis for the development of therapeutic drugs to improve the hypoxic microenvironment of RA.